2006
DOI: 10.2337/diabetes.55.04.06.db05-0932
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Aldose Reductase to Diabetic Hyperproliferation of Vascular Smooth Muscle Cells

Abstract: The objective of this study was to determine whether the polyol pathway enzyme aldose reductase mediates diabetes abnormalities in vascular smooth muscle cell (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 56 publications
5
66
0
Order By: Relevance
“…Low bone turnover has also been associated with vascular calcification in diabetic HD patients (Galassi et al, 2006), and poor glycemic control induces low bone turnover by suppressing PTH secretion (Sugimoto et al, 1990), impairing osteoblast growth (Inaba et al, 1999), and reducing the responsiveness of osteoblasts to PTH and 1,25-dihydroxyvitamin D3 (Inaba et al, 1999). A direct adverse effect of high glucose on vascular cells has also been proposed (Wadham et al, 2007;Srivastava et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Low bone turnover has also been associated with vascular calcification in diabetic HD patients (Galassi et al, 2006), and poor glycemic control induces low bone turnover by suppressing PTH secretion (Sugimoto et al, 1990), impairing osteoblast growth (Inaba et al, 1999), and reducing the responsiveness of osteoblasts to PTH and 1,25-dihydroxyvitamin D3 (Inaba et al, 1999). A direct adverse effect of high glucose on vascular cells has also been proposed (Wadham et al, 2007;Srivastava et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The role of AR in the mediation of oxidative stress-induced signaling was further confirmed in an animal model of restenosis. Restenosis of balloon -injured rat carotid arteries was significantly blocked by AR inhibitors [18,23]. Recently, we have shown that GS-DHN formed by the reduction of GS-HNE by AR could mediate cell signaling leading to activation of NF-κB and proliferation of cultured VSMC [24].…”
Section: Introductionmentioning
confidence: 99%
“…The third limitation concerns another possible route of HG-related cellular damage, namely the polyol pathway. We were unable to find reports on the effects of NAC in the modulation of polyol-related metabolism [32, 33]. Such investigations could provide additional options with therapeutic implications [34].…”
Section: Discussionmentioning
confidence: 99%